Reduced Carbon Footprint with Composite Structures. (2016) - Urian, Gabriel Mircea; Haupt-Karp, Alina
Abstract: The paper proposes to investigate the performances for composite structures made with fully encased steel-concrete composite columns in seismic zones in comparison with traditional solutions: concrete and steel to reduce carbon footprint. To achieve the proposed objectives a case study was developed on composite frames, with fully encased steel-concrete composite columns and steel beams. The case study included five types of structures, with two, six, eight, ten and twelve levels. The composite columns were designed with different types of steel contribution ratios: low, medium and high. The floor plan was the same for all composite frames used in the case study. The level height was also the same for all stories and composite frames. To evaluate the seismic performances on the studied composite frames were performed pushover and time history analysis, using the following parameters which control the chosen seismic zone: peak ground acceleration equal to 0.32 g and the corner period equal to 1.6s. The results were compared with traditional similar structures of concrete and steel. The numerical model used in all analysis was developed at Technical University of Cluj-Napoca in 2013. The model was calibrated and validated using six experimental programs taken from the international literature on fully encased steel-concrete composite columns. The three types of structures: composite, concrete and steel are compared and the main advantages and disadvantages are presented. The main focuses of the paper include modality of reducing carbon footprint, also economical and structural improvement of composite structures in comparison with traditional ones.